The Chilean Economy: Why Are We Slowing Down When We Should Be Growing? (Observatorio Económico, 2014)
The Chilean economy is slowing down; what is causing this phenomenon? Let us put on a Sherlock Holmes hat, find a good magnifying glass (eyeglasses will do as well), look for good economics books in the library, and begin the investigation. The first suspect is the tax reform (please read this paragraph in a sinister, hoarse voice; taxes are always just that: sinister and hateful, especially in April of each year). The investigation quickly reveals that the tax reform should be expansionary rather than contractionary. Yes, you read that right (do not be alarmed: in a heinous crime, suspect number one is not the main culprit). But why might a reform that raises taxes on corporate profits be expansionary? Continue reading...
Keywords: economic slowdown; economic growth; tax reform